Large Area Self‐Assembled Ultrathin Polyimine Nanofilms Formed at the Liquid–Liquid Interface Used for Molecular Separation. Issue 8 (17th January 2020) - Tiwari, Karishma; Sarkar, Pulak; Modak, Solagna; Singh, Harwinder; Pramanik, Sumit Kumar; Karan, Santanu; Das, Amitava
Abstract: Separation membranes with higher molecular weight cut‐offs are needed to separate ions and small molecules from a mixed feed. The molecular sieving phenomenon can be utilized to separate smaller species with well‐defined dimensions from a mixture. Here, the formation of freestanding polyimine nanofilms with thicknesses down to ≈14 nm synthesized via self‐assembly of pre‐synthesized imine oligomers is reported. Nanofilms are fabricated at the water–xylene interface followed by reversible condensation of polymerization according to the Pieranski theory. Polyimine nanofilm composite membranes are made via transferring the freestanding nanofilm onto ultrafiltration supports. High water permeance of 49.5 L m ‐2 h −1 bar −1 is achieved with a complete rejection of brilliant blue‐R (BBR; molecular weight = 825 g mol −1 ) and no more than 10% rejection of monovalent and divalent salts. However, for a mixed feed of BBR dye and monovalent salt, the salt rejection is increased to ≈18%. Membranes are also capable of separating small dyes (e.g., methyl orange; MO; molecular weight = 327 g mol −1 ) from a mixed feed of BBR and MO. Considering a thickness of ≈14 nm and its separation efficiency, the present membrane has significance in separation processes. Abstract : Polyimine nanofilm composite membranes are prepared by transferring freestanding polyimine nanofilms onto polyacrylonitrile support and are utilized for selective separation of dyes and salts with molecular area cut‐off of ≈1.5 nm 2 (equivalent to molecular weight cut‐off of ≈800 g mol −1 ). Nanofilms are made by self‐assembly of imine oligomers at the water–xylene interface followed by water catalyzed reversible condensation polymerization.